1996
DOI: 10.1111/j.1600-0447.1996.tb09806.x
|View full text |Cite
|
Sign up to set email alerts
|

The symptom structure of panic disorder: a trial using factor and cluster analysis

Abstract: Using cluster analysis of 207 patients with panic disorder (PD), we investigated the relationships between several panic symptoms at the time of panic attacks, which included anticipatory anxiety, agoraphobia, and 13 clinical symptoms based on the Diagnostic and Statistics Manual-III-Revised. Cluster analysis revealed three panic symptom clusters: cluster A (dyspnea, choking, sweating, nausea, flushes/chills); cluster B (dizziness, palpitations, trembling or shaking, depersonalization, agoraphobia, and anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 23 publications
2
34
1
7
Order By: Relevance
“…Previous reports on PD patients (Briggs et al (1993); Argyle and Roth (1989); De Beurs et al (1994); Cox et al (1994); Meuret et al (2006); Shioiri et al (1996)) generally agreed on several clusters, one representing a respiratory component. The similarity between our clusters, extracted in a normal sample, and clusters found in studies on PD patients supports the idea that the CO 2 challenge in healthy volunteers may be a valid model to study the phenomenology of clinical panic.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous reports on PD patients (Briggs et al (1993); Argyle and Roth (1989); De Beurs et al (1994); Cox et al (1994); Meuret et al (2006); Shioiri et al (1996)) generally agreed on several clusters, one representing a respiratory component. The similarity between our clusters, extracted in a normal sample, and clusters found in studies on PD patients supports the idea that the CO 2 challenge in healthy volunteers may be a valid model to study the phenomenology of clinical panic.…”
Section: Discussionmentioning
confidence: 68%
“…The cardiorespiratory cluster included shortness of breath, chest pain, fear of dying, palpitations, tingling, and choking. Shioiri et al (1996), in a Japanese study of 207 PD patients, found slightly different results. Their cluster analysis revealed three panic symptom clusters.…”
Section: Introductionmentioning
confidence: 94%
“…Poucos estudos fenomenológicos sobre TP têm sido realizados, a maioria em ambiente natural, não controlado. Shioiri et al 28 …”
Section: Discussionunclassified
“…During a panic attack, fear, shortness of breath, dizziness, heart palpitations, chest pain, sweating, faintness, paresthesia, nausea and cognitive symptoms including depersonalization and fear of losing control are typically reported [1]. Panic disorder is invariably associated with anticipatory anxiety [2,3] and is characterized by phobic avoidance [1]. Indeed, agoraphobic behavior routinely accompanies panic disorder and is more prevalent among females [4,5].…”
Section: Introductionmentioning
confidence: 99%